2020
DOI: 10.3390/jpm10040190
|View full text |Cite
|
Sign up to set email alerts
|

Comment: “Evaluation of the Association of Omentin 1 rs2274907 A>T and rs2274908 G>A Gene Polymorphisms with Coronary Artery Disease in Indian Population: A Case Control Study”

Abstract: The study by Jha et al. (2019) demonstrated an association of the single nucleotide polymorphism (SNP) rs2274907 A>T with coronary artery disease (CAD) in 100 CAD patients and 100 matched healthy controls from a South Indian population. There are serious concerns with regard to the interpretations of the study findings. The genotypes of the SNP are not in Hardy–Weinberg equilibrium (HWE) in both cases (p < 0.0001) and controls (p = 0.006), which is indicative of a technical error due to a problematic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…To date, the present study has been the largest (N = 1,886) to explore the association of the omentin SNP rs2274907 with cardiometabolic diseases. While majority of the studies have shown ‘T’ allele as the minor allele [ 18 , 22 , 39 , 40 ], the dbSNP database shows ‘A’ allele as the minor allele except for some of the Asian, African and European populations, which is indicative of a significant genetic heterogeneity ( https://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?do_not_redirect&rs=rs2274907 ) [ 42 ]. However, ‘A’ allele is the minor allele in our study and the dbSNP database for GIH population (Gujarati Indians in Houston, Texas, USA).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the present study has been the largest (N = 1,886) to explore the association of the omentin SNP rs2274907 with cardiometabolic diseases. While majority of the studies have shown ‘T’ allele as the minor allele [ 18 , 22 , 39 , 40 ], the dbSNP database shows ‘A’ allele as the minor allele except for some of the Asian, African and European populations, which is indicative of a significant genetic heterogeneity ( https://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?do_not_redirect&rs=rs2274907 ) [ 42 ]. However, ‘A’ allele is the minor allele in our study and the dbSNP database for GIH population (Gujarati Indians in Houston, Texas, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that healthy lifestyle may modify the association between genetic risk and metabolic disease-related traits (10)(11)(12)(13)(14)(15)(16) . Although some studies have shown that increased physical activity levels and healthy diet can attenuate the effect of genetic variants on metabolic traits, other studies have shown conflicting results (17) , which could be attributed to genetic heterogeneity and differences in the dietary patterns across multiple ethnic groups (7,18,19) . Majority of the gene-lifestyle interactions have focused on metabolic disease-related outcomes (20)(21)(22)(23) and only a few have focused on vitamins B 12 and D, two critical vitamins which have been shown to be associated with age-related cardiometabolic diseases (24) .…”
mentioning
confidence: 99%